A challenging case of hemobilia: Endovascular treatment of cystic artery pseudoaneursym secondary to acute cholecystitis: Cystic artery pseudoaneursym: A hemobilia case - Güneş, Yasin Celal; Çifçi, Bilal Egemen; Edis Özdemir, Fatma Ayça (Journal of Surgery and Medicine, 2024)
Acute cholecystitis is a leading cause of individuals seeking medical attention in the emergency department due to right upper quadrant pain. Common complications associated with this clinical condition, which is frequently encountered in daily practice, include gangrenous cholecystitis, pericholecystic abscess, cholangitis, and gallbladder perforation. It is important to also consider the rare but potentially severe complication of cystic artery pseudoaneurysm. This case report details the development of a cystic artery pseudoaneurysm secondary to acute cholecystitis and its subsequent endovascular treatment in a 59-year-old male patient with no known underlying medical conditions, in accordance with existing literature.